2015
DOI: 10.1086/684043
|View full text |Cite
|
Sign up to set email alerts
|

Do Medical Marijuana Laws Increase Hard-Drug Use?

Abstract: Medical marijuana laws generate significant debate regarding drug policy. For instance, if marijuana is a complement to hard drugs, then these laws would increase the usage not only of marijuana but also of hard drugs. In this paper I study empirically the effects of medical marijuana laws by analyzing data on drug arrests and treatment admissions. I find that medical marijuana laws increase these proxies for marijuana consumption by around 10-15 percent. However, there is no evidence that cocaine and heroin u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 68 publications
0
55
1
1
Order By: Relevance
“…Chu uses administrative data and shows that MML passage leads to a 10% to 20% increase in arrests for marijuana-related possession and substance abuse treatment admissions (Chu, 2014(Chu, , 2015. Pacula et al (2015) show that passage of an MML leads to a 14% reduction in marijuana-related substance abuse treatment admissions using the same dataset as Chu (2014) and no change in self-reported marijuana use among a sample of young adults in the National Survey of Youth 1997.…”
mentioning
confidence: 99%
“…Chu uses administrative data and shows that MML passage leads to a 10% to 20% increase in arrests for marijuana-related possession and substance abuse treatment admissions (Chu, 2014(Chu, , 2015. Pacula et al (2015) show that passage of an MML leads to a 14% reduction in marijuana-related substance abuse treatment admissions using the same dataset as Chu (2014) and no change in self-reported marijuana use among a sample of young adults in the National Survey of Youth 1997.…”
mentioning
confidence: 99%
“…Turning rst to demand, Pacula et al (forthcoming) nd that MML lead to an increase in self-reported use of marijuana. Chu (2012) shows there is a positive relationship between MML and marijuana-related arrests, indicating that when MML are in place, illegal demand for marijuana increases. Although we are not aware of a similar study in the US, Walsh et al (2013) shows that MML in Canada also substantially increase the demand for (legal) medical marijuana.…”
Section: Legal Impact Of MMLmentioning
confidence: 97%
“…Anderson et al, 2013;Chu, 2012Chu, , 2013Pacula et al, forthcoming;Morris et al, 2014;Alford, 2014). Most related to our study are Morris et al (2014), and Alford (2014) which investigate the relationship between MML and crime.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations